Оrganizational attention deficit as sustainability indicator: assessment and management - Markovska-Simoska, Silvana; Pop-Jordanov, Jordan; Pop-Jordanova, Nada; Markovska, Natasa (Industrija, 2013)
The aim of this paper is to contribute towards dealing with the attention indicator in a standard Pressure-State-Response (PSR) framework of sustainable development. Hence, the daily information overflow is identified as a pressure variable adversely affecting the attention. This is manifested by an increased likelihood of missing key information when making decisions, diminished time for attentive reflection, difficulty in holding others’ attention, as well as by decreased ability to focus when necessary, which are symptoms of the so-called organizational attention deficit disorder - OADD. As to the state variable there were combined techniques from cognitive neuroscience and applied sciences in order to objectively measure the incidence of OADD. In particular, the use of neuropsychological procedures for objective assessment of OADD will be summarized. Namely, few attention diagnostic tests of the Amsterdam Neuropsychological Tasks Program (ANT) will be considered for determining the focused, shifted and sustained attention. As intervention measure attention strengthening techniques is applied. In particular, in research were proposed the neurofeedback technique as response variable and have shown its effectiveness in coping with the OADD. This approach represents a new perspective in social psychophysiology and expands the potential applications of ANT and neurofeedback methodology.
Keywords: Measurement; Information; Sustainable development